2022
DOI: 10.1002/alz.12817
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of rest periods, astrocyte activation, and cognitive decline in older adults with and without Alzheimer's disease

Abstract: Introduction Sleep disruption is associated with astrocyte activation and impaired cognition in model organisms. However, the relationship among sleep, astrocyte activation, and cognition in humans is uncertain. Methods We used RNA‐seq to quantify the prefrontal cortex expression of a panel of human activated astrocyte marker genes in 1076 older adults in the Religious Orders Study and Rush Memory and Aging Project, 411 of whom had multi‐day actigraphy prior to death. We related this to rest fragmentation, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…Cognitive ability and learning memory are affected by a variety of factors, including age ( Yang X. et al, 2020 ), disease ( Bi et al, 2021 ), diet ( Sun et al, 2022 ), sleep ( Wu et al, 2022 ), and genetics ( Lindner et al, 2022 ). We have focused our attention on the issue of learning memory decline induced by sleep problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive ability and learning memory are affected by a variety of factors, including age ( Yang X. et al, 2020 ), disease ( Bi et al, 2021 ), diet ( Sun et al, 2022 ), sleep ( Wu et al, 2022 ), and genetics ( Lindner et al, 2022 ). We have focused our attention on the issue of learning memory decline induced by sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy sleep is essential for the rejuvenation of the animal’s body and mind, yet sleep deprivation (SD) or sleep disruption is commonplace in contemporary times due to the accelerated pace of life ( Chang et al, 2021 ; Wu et al, 2022 ). Sleep disorder syndrome known as SD occurs when a patient has trouble falling or staying asleep, and their sleep experiences worse quality, which ultimately causes problems such as cognitive decline ( Chang et al, 2009 ; Wang Z. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data showed that astrocytes not only modulate sleep but also maintain intracerebral ion and fluid homeostasis, and provide energy to neurons [ 94 ]. A cohort study found that sleep fragmentation increased astrocytic activation markers, which was associated with a lower level and faster decline of cognitive function [ 95 ]. This finding provided the initial clinical evidence that astrocytes were involved in sleep fragmentation-induced cognitive decline.…”
Section: Potential Role Of Astrocytes In Sleep Disorders Comorbiditiesmentioning
confidence: 99%
“…Astrocytes have also been implicated in the regulation of ECoG activity during different sleep states (Halassa et al 2009;Foley et al, 2017), and a higher expression of activated astrocyte marker genes in the prefrontal cortex was reported to be associated with indications of sleep disturbances and cognitive decline in humans (Wu et al, 2023). Moreover, optogenetic activation of astrocytes was recently shown to rescue sleep oscillations and fear memory in a mouse model of AD (Lee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, astrocytes play a crucial role in lipid synthesis, distribution, and storage (Lee et al, 2021; Smolič et al, 2021), and dysregulation of lipid metabolism in astrocytes can contribute to brain diseases and neurodegeneration (Chen et al, 2023; Mi et al, 2023). Astrocytes have also been implicated in the regulation of ECoG activity during different sleep states (Halassa et al 2009; Foley et al, 2017), and a higher expression of activated astrocyte marker genes in the prefrontal cortex was reported to be associated with indications of sleep disturbances and cognitive decline in humans (Wu et al, 2023). Moreover, optogenetic activation of astrocytes was recently shown to rescue sleep oscillations and fear memory in a mouse model of AD (Lee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%